LATE QUATERNARY PALEOENVIRONMENTS AND MODERN POLLEN DATA FROM WRANGEL ISLAND (NORTHERN CHUKOTKA) - Lozhkin A.V.; Belaya B.V.; Anderson P.M.; Vartanyan S.L.; Brown T.A.; Kotov A.N. (My University, 2001)
New lacustrine records from central and southern Wrangel Island are analyzed for their pollen content in an attempt to clarify possible linkages between paleoenvironmental shifts and the dwarfing and/or extinction of the island's mammoth population. A Younger Dryas-aged peat is also examined to provide better understanding of the regional climatic history. Samples of surficial lake sediments from Wrangel Island and Chukotka aid in interpreting the lacustrine records. The modern spectra differentiate the herb-dominated tundra of Wrangel Island from the shrub tundras of the mainland and are unique when compared to other arctic assemblages. Analysis of the fossil data indicates that a herb-dominated tundra has been present on southern and central Wrangel Island since at least 11 ka BP. Comparison to modern palynological data implies little change in vegetation during the Holocene. The lacustrine interpretations contrast to those based on paleobotanical study of peats and alluvium, which suggest modern vegetation was not present until ca 4–3 ka BP. Pre-Holocene assemblages have high percentages of Cyperaceae pollen, perhaps indicating more moderate conditions. Summer climate is inferred to be warmer and moister than present during the latest Pleistocene and early Holocene. The pattern of postglacial warming on Wrangel Island is more like that from eastern Beringia than from other areas of western Beringia. Modern synoptic anomaly maps indicate that such a climatic pattern is reasonable and related to the presence of negative anomalies over western Beringia and a region of weaker positive 500 mb pressure centered over the Beaufort Sea.
Keywords: Holocene; Pleistocene; Кайнозой::Четвертичная::Плейстоцен; Cenozoic::Quaternary::Holocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Голоцен